Management of intellectualization of innovative enterprises personnel of industry as direction of research: relevance, features, results - E. V. Yakovleva (Омский научный вестник: Серия "Общество. История. Современность")
The relevance of management of intellectualization of personnel of the enterprises of the industry of innovative type at the present stage of economic and technological development is considered, its features are revealed causing specifics of management and also the received results of a research at various levels reveals: theoretical, methodological, methodical and practical. The research objective assumes realization of the corresponding tasks is the solution of a scientific problem of formation of intellectual infrastructure of innovative activity in the industrial sector of national economy